2022
DOI: 10.1094/phyto-03-21-0113-r
|View full text |Cite
|
Sign up to set email alerts
|

SeedborneCercospora beticolaCan Initiate Cercospora Leaf Spot from Sugar Beet (Beta vulgaris) Fruit Tissue

Abstract: Cercospora leaf spot (CLS) is a globally important disease of sugar beet (Beta vulgaris L.) caused by the fungus Cercospora beticola. Long-distance movement of C. beticola has been indirectly evidenced in recent population genetic studies, suggesting potential dispersal via seed. Commercial sugar beet “seed” consists of the reproductive fruit (true seed surrounded by maternal pericarp tissue) coated in artificial pellet material. In this study, we confirmed the presence of viable C. beticola in sugar beet frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…They discovered both bacterial and fungal DNA in the seed coat (=fruit) that showed specific band patterns depending on seed acreage, which was correlated with differing germination rates under field conditions. Bacterial seed communities appeared to be complex, while fungal communities seemed to be species-poor (Dent et al, 2004 ; Spanner et al, 2021 ). A commonality in bacterial sugar beet seed communities with other plant species is the high abundance of Pseudomonas and Pantoea (Truyens et al, 2015 ; Nelson, 2018 ; Wassermann et al, 2019a ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%
See 2 more Smart Citations
“…They discovered both bacterial and fungal DNA in the seed coat (=fruit) that showed specific band patterns depending on seed acreage, which was correlated with differing germination rates under field conditions. Bacterial seed communities appeared to be complex, while fungal communities seemed to be species-poor (Dent et al, 2004 ; Spanner et al, 2021 ). A commonality in bacterial sugar beet seed communities with other plant species is the high abundance of Pseudomonas and Pantoea (Truyens et al, 2015 ; Nelson, 2018 ; Wassermann et al, 2019a ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%
“…Other genera contribute to the bacterial seed community to various extents, including Paenibacillus, Sphingomonas, Curtobacterium, Massilia, Methylobacterium, Saccharibacillus , and Kosakonia (Wolfgang et al, 2020 ). Some fungal taxa known for phytopathogenic traits, e.g., Cercospora, Fusarium , and Alternaria , can establish in seeds via the xylem sap flow (Spanner et al, 2021 ), with negative implications for the next sugar beet generation. Archaea represent 0–1.1% relative abundance and mainly comprise Woesearchaeia , indicating a minor role of Archaea in seeds (Wolfgang et al, 2020 ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiology of CLS has been well studied (Imbusch et al, 2021; Rossi et al, 2000; Tedford et al, 2018; Wolf and Verreet, 2005). C. beticola is polycyclic, with the primary inoculum coming from four known sources, including overwintering structures called pseudostromata which can persist on plant debris for two years (Khan et al, 2008), windborne conidia blowing in from outside newly planted fields, conidia produced on alternative hosts growing in or nearby new fields, and infested seeds (Spanner et al, 2022). In as little as 7 days these first infections can reproduce asexually to form conidia that establish secondary infections (Rangel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The primary site of infection is leaves, CLS infections did not establish on roots and stems inoculated with spores (Khan et al, 2008). The primary inoculum can come from multiple sources, including overwintering structures called pseudostromata, which can persist on plant debris for 22 months (Khan et al, 2008), conidia produced on alternative hosts growing in or nearby new fields, and infested seeds (Spanner et al, 2022). Previous work in the USA found that even when there is no crop rotation, genotypes were not resampled over time, suggesting that the dominant source of inoculum for an epidemic is external to the field of interest (Knight et al, 2018).…”
Section: Introductionmentioning
confidence: 99%